Mesostructural materials on a base of tin oxides and vanadium - Швець, О.В.; Заруба, Л.М.; Мишастий, А.Ю.; Ільїн, В.Г. (Proceedings of National Aviation University, 2005)
Some series of mesostructural materials on a base of tin oxide and phosphate (templates – cetyltrimethylammonium bromide, cetylpyridinium bromide, dodecylamine, sodium dodecylsulfate and polyethylenoxide–polypropylenoxide–polyethylenoxide triblockcopolimer Pluronic 123) were obtained. The possibility of control of mesostructure type (hexagonal, wormlike, lamellar) and ordering degree by change of template nature, template/Sn ratio, pH and kind of reactionary medium, ageing duration, hydrothermal treatment is shown. Optimal conditions of template removal and creation of mesoporous materials on a base of tin oxide with narrow pore distribution (± 4 Å) over the range D = 22–44 Å, SBET=120–550 m2/g and Vpore till 0,23 cm3/g were determined. The influence of synthesis conditions, in particular, pH of reaction medium, duration of synthesis, ratio of main components, the nature of template, temperature of hydrothermal treatment on formation of lamellar, cubic and disordered hexagonal mesostructures with different degree of crystallinity was studied. The influence of magnesium, cobalt, zinc and cadmium on formation of mesophases and own crystallization of vanadium oxide was shown. Calcinations at 380 °C in argon flow gave mesoporous materials with pore diameter between 27–80 Å, Vпор = 0,10–0,30 cm3/g, SBET=80–200 m2/g .